The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1365-2486.2010.02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of both photosynthesis and respiration in response to warmer and drier conditions in a boreal peatland ecosystem

Abstract: Peatland ecosystems have been consistent carbon (C) sinks for millennia, but it has been predicted that exposure to warmer temperatures and drier conditions associated with climate change will shift the balance between ecosystem photosynthesis and respiration providing a positive feedback to atmospheric CO 2 concentration. Our main objective was to determine the sensitivity of ecosystem photosynthesis, respiration and net ecosystem production (NEP) measured by eddy covariance, to variation in temperature and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
114
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 64 publications
13
114
4
Order By: Relevance
“…However, the steady state of total carbon for the first 100 years following 40-cm water table decline was consistent with Sulman and others (2009) and Flanagan and Syed (2011), who observed no change in NEE over short time scales following drainage of that magnitude in peatlands. In simulations that included only soil effects, the model did predict substantial losses of carbon for both depths of water table decline, indicating that the major difference between our simulations and short-term, soil-focused studies was the inclusion of plant community changes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, the steady state of total carbon for the first 100 years following 40-cm water table decline was consistent with Sulman and others (2009) and Flanagan and Syed (2011), who observed no change in NEE over short time scales following drainage of that magnitude in peatlands. In simulations that included only soil effects, the model did predict substantial losses of carbon for both depths of water table decline, indicating that the major difference between our simulations and short-term, soil-focused studies was the inclusion of plant community changes.…”
Section: Discussionsupporting
confidence: 89%
“…Increased plant growth resulting from declining water table has been observed in field studies over inter-annual time scales (Sulman and others 2009;Flanagan and Syed 2011), although Strack and others (2006) observed variations in the response between hummock, hollow, and lawn microforms. Wetland succession studies over decadal time scales have observed large increases in biomass as sedge, shrub, or moss-dominated wetland landscapes are converted to forest (Laine and others 1995;Laiho and others 2003).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Schuur et al (2008)) and negative (e.g. Flanagan and Syed (2011)) feedback loops between climate warming and the carbon cycle in the Arctic leads to considerable uncertainties in how far the substrate potential in permafrost deposits plays a key role for future greenhouse gas production concerning shifts in the microbial 25 community composition, vegetation, hydrogeology and soil thermal regime. This study shows that OM especially deposited during the interstadial and glacial periods appear to contain a larger substrate potential than the interglacial deposits.…”
Section: Microbial Substrate Potential For Greenhouse Gas Generationmentioning
confidence: 99%